MENELAAH UNSUR BUKU FIKSI DAN NONFIKSI KELAS VIII MTsS NAGARI GANTUNG CIRI - Umeru, Jerli Indah; Wirasty B., Rini; Putri, Mega (JELISA (Jurnal Edukasi dan Literasi Bahasa), 2023)
This research was motivated by the fact that class VIII students at MTsS Nagari Gantung Ciri had difficulty understanding between fiction and non-fiction books and their division including the elements within them. This research aims to describe the ability to study the elements of fiction and non-fiction books for class VIII students at MTsS Nagari Gantung Ciri for the 2022/2023 academic year. Data collection techniques are: the teacher gives fiction and non-fiction discourse to students, the teacher gives students time to read fiction and non-fiction discourse for approximately 20 minutes, the teacher explains the material of the two books, the teacher checks students' understanding of the books they have read, the students Answering questions on a sheet of paper, the teacher asks students to collect the answer sheets they have worked on. Data analysis techniques are: the researcher reads the student's test results, the researcher examines the student's answer sheet which has been done based on the assessment indicators, the researcher determines the student's score, the researcher converts the raw score into a value, describes the student's ability to examine elements of fiction and non-fiction books, describes the student's ability in examining the elements of fiction and non-fiction books on a scale of 10, making histograms, concluding research results in the form of a thesis. Based on the research that has been carried out, it can be seen that (1) students' ability to examine the intrinsic elements of fiction books is in good qualifications with an average score of 81.58. (2) students' ability to examine nonfiction elements is in good qualifications with an average score of 81.74. So, it can be concluded that students' ability to examine elements of fiction and non-fiction books for class VIII students at MTsS Nagari Gantung Ciri for the 2022/2023 academic year is in good qualifications with an average of 81.66.